Efeitos Patrimoniais Especiais do Casamento nos Regimes da Comunhão: Cônjuges Titulares de Participações Sociais em Sociedades por Quotas ou Comerciantes - Martins, Cláudia Sofia Antunes (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2016)
In the present work we will expose some of the particular legal consequences of the marriage when one member of the couple is a member of a type of a commercial company called “sociedade por quotas” or dedicates his life to a commercial activity.